2008
DOI: 10.1007/s10995-008-0437-y
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Symptoms of Depression and Contraceptive Method Choices Among Low-Income Women at Urban Reproductive Health Centers

Abstract: Among adult women of reproductive age, research has focused on depression symptoms after unintended pregnancy, or associated with hormonal contraceptive method use, with little focus on depression as a predictor of unintended pregnancy. This study was conducted to identify mental and behavioral health characteristics associated with use of less effective contraceptive methods. Choosing a less effective method of contraception places sexually active women who are not seeking pregnancy at increased risk of unint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 24 publications
2
40
2
Order By: Relevance
“…Previous studies found that elevated levels of anxiety or depression had been associated with sexual risk-taking behaviour such as inconsistent condom use. 34,35 Other studies 24,25 found that women's psychological symptoms predicted their contraceptive non-use and use of less effective methods. We did not however assess the type of contraceptive method used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies found that elevated levels of anxiety or depression had been associated with sexual risk-taking behaviour such as inconsistent condom use. 34,35 Other studies 24,25 found that women's psychological symptoms predicted their contraceptive non-use and use of less effective methods. We did not however assess the type of contraceptive method used.…”
Section: Discussionmentioning
confidence: 99%
“…13 Among university students factors associated with contraceptive non-use for women, men or both can be summarized as follows: 1) socio-demographic factors (younger age, lower educational level 10,14,15 , being male 16 , higher degree of religiosity 17,18 , high price of contraceptives 14 ); 2) Sexual behaviour (early sexual debut 10,16,19 , not previously pregnant 20 , more than one sexual partner in the past 12 months 20 , internet use (sex) 21,22 ; Psychosocial factors or internal assets (low locus of control, low personal initiative and assertiveness 14 , lack of life satisfaction 23 , and psychological distress 24,25 ), and 3) other factors (fear of side effects of modern contraceptives 7 , lack of exposure to healthcare worker talking about contraception 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found conflicting associations between mental health and contraceptive choice in the nonabortion setting. One study found that women who screened positive for depression were less likely to choose a hormonal contraceptive than women without depression [37]. Another found that, among contraceptive users, those who reported 14 or more days of poor mental health in the previous 30 days were more likely to have chosen permanent contraception in the past [38].…”
Section: Discussionmentioning
confidence: 99%
“…There may be differences in the frequency of use of these other forms of contraception according to the presence of chronic disease. 38,39 Although the NAMCS is a national survey with complex sampling designed to provide reliable information about the delivery of health care in outpatient practices across the country, the quality of the data are limited by the survey response rate and whether the selected Ն30 records obtained from each practice are truly representative of the patient population. Nevertheless, the systematic and random sampling strategy used by the NAMCS would be expected to reduce any nondifferential bias based on the presence of CVRFs.…”
Section: Discussionmentioning
confidence: 99%